Flexoelectric Effect: Controllable, Self‐Powered, and High‐Performance Short‐Wavelength Infrared Photodetector Driven by Coupled Flexoelectricity and Strain Effect (Small Methods 7/2021). Issue 7 (14th July 2021) - Kumar, Mohit; Lim, Jaeseong; Park, Ji‐Yong; Seo, Hyungtak
Abstract : In article number 2100342, Hyungtak Seo, and co‐workers demonstrated the flexoelectric effect‐driven self‐powered giant short‐wavelength infrared photoresponse from centrosymmetric bulk silicon. By precisely controlling the applied force, the infrared response sensitivity is controlled across a large range while maintaining exceptionally high sensitivity, good responsiveness, and quick response speed, even at the nanoscale.